Adherence to GOLD guidelines in COPD patients at a tertiary hospital - Kaftel, Steven (My University, 2020)
ABSTRACT Background: The Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines, updated in 2019, provide a framework to classify chronic obstructive pulmonary disease (COPD) severity. In so doing, it guides practitioner’s choice of therapy for the individualized patient. The GOLD guidelines classify patients into one of four groups: A, B, C, or D. This is based on symptoms, as well as exacerbations or hospitalizations. Inhaled corticosteroids (ICS) should be reserved for GOLD C and D patients who have frequent exacerbations (≥2/year). Aims: The primary objective of this research is to document adherence to GOLD treatment guidelines in COPD patients at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) respiratory clinic. The secondary objective of the study is to investigate whether a statistically significant association exists between GOLD category and lack of adherence to guidelines, as well as GOLD category and inappropriate use of ICS. Methods: A retrospective record review of patients with COPD attending respiratory clinic over a three month period at CMJAH was conducted. Descriptive analysis of the data was carried out as follows: categorical variables were summarized by frequency and percentage tabulation and illustrated by means of bar charts. Continuous variables were summarized by the mean, standard deviation, and their distribution illustrated by means of histograms. The Chi Square test was used to assess the relationships between categorical variables and the Fisher’s exact test when the sample size was small. Results: A total of 146 patients were included in the study. In 54.1% of cases the modified Medical Research Council (mMRC) classification of breathlessness was not recorded in the notes. The majority of the patients (72.6%) were classified as Group B. Furthermore, 87.7% of the total patient cohort were using ICS or ICS/long acting beta 2 agonist (LABA) combination therapy, and 61.0% of patients were using triple therapy: long acting muscarinic antagonist (LAMA), LABA, and ICS. Only 24.7% of patients were found to be receiving treatment adherent to GOLD guidelines with respect to appropriate use of ICS. There was a significant association between GOLD category and a lack of adherence to GOLD treatment guidelines (p<0.0001) with nonadherence to guidelines being much higher in group B with a significant percentage of patients (87%) on inappropriate ICS therapy. Conclusions: Adherence to GOLD guidelines and therapeutic algorithms was lacking in this cohort of patients studied. The mMRC classification of breathlessness was poorly recorded in the patients’ notes despite the fact that it forms a core part of the GOLD classification. In addition, the majority of patients are treated with ICS therapy. This may be as a result of the lack of the appropriate patient classification according to the GOLD criteria. This limitation has probably resulted in the injudicious use of ICS therapy with the potential for an increased risk of side effects such as pneumonia. In order to prevent this, we should be implementing strategies to ensure that the GOLD classification is correctly recorded at each clinic visit by means of a standard data collection sheet. This will prevent over treatment of patients, reduce the use of unnecessary inhalers and the cost thereof in a resource constrained setting, as well as potentially reduce the complications and side effects of ICS therapy. The use of serum eosinophil counts as a validated biomarker may help to guide practitioners to decide which patients to attempt withdrawal of ICS therapy
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine, 2020